The effects of cooperative learning instruction on the comprehension of narrative text among ESL learners / Hasnah Razali - Razali, Hasnah (2004)
The in-depth nature of this study gives an integrated picture of the role of cooperative learning instruction in ESL comprehension of a short story, i.e. a form of narrative text. The study aimed to examine three aspects of a short story comprehension using cooperative learning instruction among form four secondary school ESL learners. The research questions are: 1) Is there any significant difference in the performance of the ESL students’ reading comprehension of a short story in terms of plot, characterization and theme due to cooperative learning instruction?, 2) Is there any significant difference in the overall performance of the ESL students’ reading comprehension of a short story due to cooperative learning instruction? and 3) What are the ESL students’ perceptions of cooperative learning instruction on their comprehension of a short story? A total of 72 ESL students from two classes of a secondary school participated in the study. One form four class formed the experimental group, and the other formed the control group. The ESL students in the experimental group used the cooperative learning instruction in comprehending the short story, while the ESL students in the control group used the individualistic traditional learning instruction. Two types of tests were used: a) literary test, and b) pretest and posttest. The analyses of data for this study involved the calculation of the differences in performance between the experimental and the control groups in the literary test in terms of plot, characterization and theme of the short story. Statistical analyses of the data revealed three important findings. Firstly, the ESL students in the experimental group performed better than the control group in understanding the plot, characterization and theme of the short story. Secondly, the cooperative learning instruction had significant facilitative effect on the ESL subjects’ overall comprehension performance of the short story. Thirdly, the subjects in the experimental group had positive perception towards cooperative learning instruction in comprehending a short story. In general, the current study fully supports the use of cooperative learning instruction for improving ESL students’ comprehension of a short story which is one type of narrative text.